2014
DOI: 10.1353/hpu.2014.0145
|View full text |Cite
|
Sign up to set email alerts
|

Do Our Patients Have Enough to Eat?: Food Insecurity among Urban Low-income Cancer Patients

Abstract: This study assessed the prevalence and predictors of food insecurity among a cohort of underserved oncology patients at New York City cancer clinics. A demographic survey and the U.S. Household Food Security Survey Module were administered. A multivariate General Linear Model Analysis of Covariance was used to evaluate predictors of food insecurity. 404 completed the surveys. 18% had very low, 38% low, 17% marginal, and 27% high food security. The Analysis of Covariance was statistically significant (F(7, 370)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 33 publications
1
55
0
Order By: Relevance
“…We consulted with experts in food insecurity and chronic conditions to select 9 chronic health conditions for our study. All these conditions were previously identified in the literature as associated with food insecurity or high health care use and costs (13,2022). The 9 chronic health conditions were hypertension, coronary heart disease, stroke, emphysema, asthma, cancer, chronic bronchitis, arthritis, and diabetes.…”
Section: Methodsmentioning
confidence: 96%
“…We consulted with experts in food insecurity and chronic conditions to select 9 chronic health conditions for our study. All these conditions were previously identified in the literature as associated with food insecurity or high health care use and costs (13,2022). The 9 chronic health conditions were hypertension, coronary heart disease, stroke, emphysema, asthma, cancer, chronic bronchitis, arthritis, and diabetes.…”
Section: Methodsmentioning
confidence: 96%
“…Many studies have reported the associations between food insecurity and unfavorable health outcomes [5,6,7,8,9,10,11]. Food insecurity can cause malnutrition due to inadequate nutrient intake [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity can cause malnutrition due to inadequate nutrient intake [5,6]. In addition, food insecurity is related to various chronic diseases, such as obesity [7], diabetes [8,9], hypertension [8], asthma [10], and cancer [11]. However, most studies have focused on socioeconomically vulnerable groups, such as children or low-income populations [6,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Ascribing no-shows to the patient's "culture" does not fix the problem. Professionals who observe access problems for some patient populations should ask: The literature on the social determinants of health includes studies of structural problems affecting health care access or patients' ability to complete needed treatment [13]. Discussing an article from this literature may help clinicians, including medical social workers often responsible for working with patients to resolve access problems, to identify similar problems in their own setting, and, whenever possible, to identify structural solutions, such as more flexible scheduling or investments in care coordination so patients can receive services closer to where they live or work.…”
Section: Avoiding Cultural Explanations For Structural Problemsmentioning
confidence: 99%